1H NMR-based DS determination of barley starch sulfates prepared in 1-allyl-3-methylimidazolium chloride. (20th January 2016) - Kärkkäinen, Johanna; Wik, Tiia-Riikka; Niemelä, Matti; Lappalainen, Katja; Joensuu, Päivi; Lajunen, Marja
Highlights: The realistic DS of starch sulfate using the integration of the 1 H NMR spectrum. Successful preparation of starch sulfates in [AMIM]Cl ionic liquid. An efficient optimization of starch sulfation using an experimental design. Abstract: The use of natural resources in a development of products and materials is currently increasing. Starch is one of the investigated resources due to its bioavailability, biodegradability, safety and affordability. In this study, native barley starch was sulfated using a SO3 -pyridine complex. The reaction was carried out for the first time using 1-allyl-3-methylimidazolium chloride ionic liquid, an excellent solvent for the starch modification. Reaction conditions (temperature, time and amount of the reagent) were studied using an experimental design. Starch sulfates with the degree of substitution (DS) 1.37 were obtained when the reaction was carried out at 40 °C for 75 min with 4:1 molar ratio of SO3 -pyridine complex:anhydroglucose unit. The determination of DS was based on 1 H NMR instead of elemental analysis, which showed overestimated DS values in this study. Starch sulfates were analyzed with FTIR and HPLC, which showed that products contained small and large sulfated molecules.